Inverse nodal problem for differential operator with eigenvalue in the boundary condition (vol 21, pg 1301, 2008) - Koyunbakan, Hikmet (Pergamon-Elsevier Science Ltd, 2009)
In this paper, some mistakes in the paper which is cited in the title are corrected. Fortunately, the mistakes do not affect the validity of the main results. (C) 2009 Elsevier Ltd. All rights reserved.